Blurring the Definition of Employment Relations in Russia: Case Law on the General Notion and Some Atypical Forms of Labor - Lyutov, Nikita (Teisė, 2019)
Transformation of Russian labour law in the last decades shows the clear trend to differentiation and fragmentation with constantly growing number of special norms covering specific (atypical) types of employment relationships. At the same time modern labour law reflects only some of recently appearing forms of employment, such as temporary agency work or telework. The paper deals with the definition of labor relations and some atypical forms of employment.